Cre-Recombinase Dependent Germline Deletion of a Conditional Allele in the Rgs9cre Mouse Line - Liput, Daniel J. (Frontiers in Neural Circuits, 2018)
Cre-LoxP conditional knockout animals have become a prominent tool to understand gene function in discrete cell-types and neural circuits. However, this technology has significant limitations including off target cre-dependent recombination. The Rgs9cre strain has been used to generate a conditional knockout in striatal medium spiny neurons, but, as presented in the current study, off target recombination in the germline results in nonconditional deletion of LoxP alleles. Using a Rem2 conditional allele, germline deletion was observed in a sex dependent manner. When Cre and LoxP alleles were co-inherited from the female parent, 27 of 29 LoxP alleles were recombined, but when co-inherited from the male parent, 5 of 36 LoxP alleles were recombined. Rem2 expression measured by RT-qPCR confirmed nonconditional recombination in extrastriatal nuclei. Cre-LoxP is a powerful technique to modify genomic DNA, however careful characterization of these mice is required to confirm control of conditional recombination.